Corticosteroids 2018
DOI: 10.5772/intechopen.72721
|View full text |Cite
|
Sign up to set email alerts
|

Action Mechanisms and Pathophysiological Characteristics of Cortisol in Horses

Abstract: Cortisol (CORT), also known as stress hormone, plays a vital role in physiological processes such as electrolyte and fluid balance, cardiovascular homeostasis, carbohydrate, protein and lipid metabolism, immune and inflammatory responses, and sexual development and reproduction. Cortisol levels are influenced by various physiological factors such as race, age, circadian rhythm, seasonality, exercise and pregnancy. Also, some stressful conditions including isolation or transport, among others, modify levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 123 publications
(194 reference statements)
1
1
0
Order By: Relevance
“…In horses, moderate-intensity exercise has been shown to increase circulating cortisol ( Ambrojo et al, 2018 ), which is in agreement with the results of the current study. However, in the current study, serum cortisol in SCFP horses returned to pre-SET levels more quickly and was significantly lower at 6 h post-SET than in CON horses.…”
Section: Discussionsupporting
confidence: 93%
“…In horses, moderate-intensity exercise has been shown to increase circulating cortisol ( Ambrojo et al, 2018 ), which is in agreement with the results of the current study. However, in the current study, serum cortisol in SCFP horses returned to pre-SET levels more quickly and was significantly lower at 6 h post-SET than in CON horses.…”
Section: Discussionsupporting
confidence: 93%
“…The ECD is the most prevalent endocrine condition affecting 20-25% of elderly horses over the age of 15 years [34,54,63,[68][69][70]. ECD is characterized by a long-term elevation in circulating glucocorticoids [63], however, plasma cortisol concentration is typically within the normal range or even lower [71]. Some research suggests that the paradox of normal plasma cortisol concentration in horses with ECD may be best explained by alterations in cortisol metabolism [28].…”
Section: Cortisol In Horse's Welfare and Healthmentioning
confidence: 99%
“…In addition to the methods mentioned above, cortisol can also be obtained from various other matrices such as urine, tears, or hooves. Urine cortisol concentration provides insights into the horse's stress response over a slightly longer duration than blood cortisol, making it valuable for assessing stress associated with specific situations [125], whereas cortisol concentration in tears was reported to rise concurrently with blood cortisol after ACTH stimulation [71]. These studies may often involve a limited number of animals, but the results are frequently reported in the context of the coping theory, focusing on stereotypical behavior as a potential sign of poor welfare.…”
Section: Other Cortisol Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of training is to improve the performance of athletes. The blood plasma cortisol concentration (CORT) seems worthy for consideration as a parameter for performance diagnosis due to its wide spectrum of actions within the energy delivering systems and many other functions (Ferlazzo and Fazio 1997, Ambrojo et al 2018, Ferlazzo et al 2020. In addition, CORT is widely accepted as a marker of stress (Cayado et al 2006, Schmidt et al 2010, Lorello et al 2017, Bohák et al 2018) and used as a marker of overtraining (Golland et al 1999, de Graaf-Roelfsema et al 2007) which is frequent in Standardbred racehorses (Tyler et al 1996).…”
Section: Introductionmentioning
confidence: 99%